Fluorescence Imaging in Second Near‐infrared Window: Developments, Challenges, and Opportunities. Issue 11 (15th September 2022) - Liang, Weijun; He, Shuqing; Wu, Si
Abstract : Fluorescence imaging is a noninvasive technique that affords real‐time fast feedback, high sensitivity, and harmless radiation and is thus effective in visualizing the anatomy and function of organs. Recently, second near‐infrared (NIR‐II, 1000–1700 nm) fluorescence imaging emerged as a popular imaging technique for both fundamental research and clinical practice, with strong potential for applications in the field of biomedicine. It affords a high signal‐to‐noise ratio and high spatial and temporal resolutions for the imaging of deep tissue owing to reduced scattering, minimal absorption, and negligible autofluorescence. Herein, the performance and advancement of fluorophores for NIR‐II fluorescence imaging are summarized. Further, the challenges to the NIR‐II fluorophores in terms of emission wavelengths, quantum yields, stability, targeting, and biocompatibility are discussed. Finally, perspective on the current development and the orientation for future studies on NIR‐II imaging, such as dual‐mode imaging, multiplexed imaging, surgical navigation, integrated diagnosis and treatment, and biosensing are discussed. Abstract : In this perspective article, recent progress of second near‐infrared (NIR‐II, 1000–1700 nm) fluorophores for biomedical applications is summarized, and the challenges and opportunities of this field are discussed.